2011
DOI: 10.1016/j.molbiopara.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Central carbon metabolism of Plasmodium parasites

Abstract: The central role of metabolic perturbation to the pathology of malaria, the promise of antimetabolites as antimalarial drugs and a basic scientific interest in understanding this fascinating example of highly divergent microbial metabolism has spurred a major and concerted research effort towards elucidating the metabolic network of the Plasmodium parasites. Central carbon metabolism, broadly comprising the flow of carbon from nutrients into biomass, has been a particular focus due to clear and early indicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 117 publications
5
74
0
Order By: Relevance
“…In support of this observation, studies in Schistosoma japonicum-infected mice exposed to artemether also showed an effect of drug treatment on important glycolytic enzymes in the parasite (39,40). In general, these findings are consistent with the vital and essential role that glycolytic enzymes play in supporting rapid growth and proliferation, similar to that seen in other rapidly proliferating cells, such as cancer cells (41,42). The high glycolytic flux of intraerythrocytic developmental cycle maintains rate-limiting glycolytic intermediates to support other pathways (e.g., nucleotide and lipid biosynthesis) (Fig.…”
Section: Resultssupporting
confidence: 85%
“…In support of this observation, studies in Schistosoma japonicum-infected mice exposed to artemether also showed an effect of drug treatment on important glycolytic enzymes in the parasite (39,40). In general, these findings are consistent with the vital and essential role that glycolytic enzymes play in supporting rapid growth and proliferation, similar to that seen in other rapidly proliferating cells, such as cancer cells (41,42). The high glycolytic flux of intraerythrocytic developmental cycle maintains rate-limiting glycolytic intermediates to support other pathways (e.g., nucleotide and lipid biosynthesis) (Fig.…”
Section: Resultssupporting
confidence: 85%
“…apicomplexan mitochondrion in energy generation has remained unclear, given the glucosereplete intracellular nature of the environmental niches of these parasites and the apparent reduction of mitochondrial metabolic pathways [4][5][6][7]. For example, apicomplexan mitochondria lack 'type I' NADH dehydrogenase (NDH, complex I of the ETC) and many apparently lack the enzymes and transporters required for fatty acid b-oxidation [8,9].…”
Section: Pages 15mentioning
confidence: 99%
“…In the inner mitochondrial membrane, the electron transport chain uses high-energy electrons to harness energy in the form of ATP. In the mitochondria of asexual Plasmodium parasites, however, the electron transport chain is not a primary source of ATP and the parasite instead relies on glycolysis for most of its ATP production (107). Indeed, little of the parasitic glucose supply is completely oxidized, and glucose is instead excreted as lactic acid (108,109).…”
Section: Coenzyme Q (Ubiquinone)mentioning
confidence: 99%